Enhancing archery-specific physical fitness: A controlled trial on the effects of medicine ball load variations - Wattimena, Ferry Yohannes; Humaid, Hidayat; Lubis, Johansyah; Pratama, Oktavian Serka Yudha; Resmana, Dadan (UIR Press, 2025)
Background: Precision sports like archery require high levels of balance and upper limb muscular endurance to maintain bow stability and aiming accuracy. While general strength training is often applied, research specifically investigating targeted physical conditioning methods—such as medicine ball load variations tailored for archers—is still limited. Research Objectives: This study aimed to evaluate the effectiveness of medicine ball training on balance and upper limb muscular endurance among collegiate archery athletes. Methods: A total thirty university-level archers voluntarily participated and were randomly divided into three groups: a 3 kg medicine ball training group (MTG), a 4 kg medicine ball training group (MFG), and a control group (CAG), each consisting of 10 participants. A pretest and posttest true experimental design was applied over eight weeks of training. Finding/Results: Both MTG and MFG groups showed significant improvements in balance and upper limb muscular endurance (p < 0.05), while the control group showed no significant changes. However, no statistically significant difference was found between the two experimental groups, indicating that both 3 kg and 4 kg medicine ball loads were similarly effective. Conclusion: Medicine ball training—regardless of moderate load variation—is effective in enhancing archery-relevant physical fitness, particularly balance and muscular endurance. These findings support the integration of medicine ball exercises into archery training programs as a practical and evidence-based strategy. Future studies should examine load progression, gender-specific responses, and long-term performance outcomes.